(untitled) (Prithvi Academic Journal, 2026)
This study investigated the kinetics of alkaline hydrolysis of ethyl caprylate at different temperatures from 20 °C to 40 °C, differing by 5 °C and 40% to 80% acetone composition in aqueous acetone binary media. It evaluates specific reaction rate, iso-composition activation energy, thermodynamic activation parameters, and isokinetic temperature by using laboratory experimental design, volumetric method of analysis and titration technique. A controlled laboratory experimental design, volumetric method of analysis and titration technique were used to study the alkaline hydrolysis of ethyl caprylate. The specific reaction rate (k) measured by using second order kinetic equation was decreased gradually with increasing percentage of acetone in aqueous-acetone media. Iso-composition activation energy (Ec) required for alkaline hydrolysis of ethyl caprylate was found to be decreased with increasing composition of acetone in reaction media. The recorded value of free energy of activation (∆G∗), known as solvolysis of ethyl caprylate, was decreased very slowly with increasing composition of acetone in reaction media. Evaluated values of enthalpy of activation (∆H∗) for hydrolysis reaction were also decreased with increasing % of acetone in reaction. The observed value of entropy of activation (∆S*) for hydrolysis of ethyl caprylate in alkaline medium was reduced differently. Observed value of entropy of activation was decreased from positive values to zero and then negative values at 70% and 80% composition of acetone in water acetone binary solvent system. The value of enthalpy of activation (∆H∗) was compensated by the value of entropy of activation (∆S*) in alkaline ester hydrolysis reaction. The recorded isokinetic temperature for alkaline hydrolysis of ethyl caprylate was found to be 291.7 Kelvin indicating slightly weak solvent-solute interaction in the binary reaction media. The study concluded that the values of specific reaction rate and thermodynamic activation parameters for alkaline hydrolysis o